2011
DOI: 10.17221/163/2010-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

What is the importance of social capital in Czech agriculture? An analysis of selected components

Abstract: Abstract:The paper examines the role of social capital in czech agricultural sector. it is argued that social capital, just like economic capital, can be employed as a resource for the improvement of economic performance of agricultural enterprises. This hypothesis is tested on a sample of primary data and an analysis of the selected indicators of social capital is presented. These include personal social networks, membership in agricultural associations and access to sources of information. Following the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The relationship between social capital and agency theory was examined in the work of Beccera and Gupta [52], who concluded that the lower the social capital (measured by trust), the higher the agency costs. According to Pospech and Spešna [53], social capital, especially informal personal ties, has a positive influence on the economic performance of firms in the agricultural sector. In addition to these, there have been a number of other studies analyzing the relationship between social capital and firm performance [54][55][56].…”
Section: Hypothesis 15 (H15) Social Capital Influences Agency Costsmentioning
confidence: 99%
“…The relationship between social capital and agency theory was examined in the work of Beccera and Gupta [52], who concluded that the lower the social capital (measured by trust), the higher the agency costs. According to Pospech and Spešna [53], social capital, especially informal personal ties, has a positive influence on the economic performance of firms in the agricultural sector. In addition to these, there have been a number of other studies analyzing the relationship between social capital and firm performance [54][55][56].…”
Section: Hypothesis 15 (H15) Social Capital Influences Agency Costsmentioning
confidence: 99%
“…This is because not many respondents are involved and actively participate in community organizations such as farmer groups and other organizations. Pospěch & Spěšná (2011) confirms that social capital has a very important role, social capital, as well as economic capital, can be used as a resource for improving the economic performance of agricultural enterprises. Social capital that is manifested in interaction patterns both vertically and horizontally will create work comfort and foster trust as individuals and institutions, thus giving birth to the strength to improve performance.…”
Section: Social Capitalmentioning
confidence: 76%
“…Self-confidence and good planning for businesses and investments are crucial for success in entrepreneurship [25]. Social capital (social networks, participation in agricultural institutions and access to information) also has its importance [26]. Information, communication and technology (ICT) may be a useful way to promote and increase farming and rural entrepreneurship [27]; however, there is still some work to be done in these fields, namely to overcome several constraints that complicate their utilization by farmers and other agricultural stakeholders [28].…”
Section: Some Concepts Associated With Farming Entrepreneurshipmentioning
confidence: 99%